Transition to IFRS 9 : Practical Guidance for the Foreign Reserves of Central Banks - Ha, Yunjung S. (World Bank, Washington, DC, 2017)
This paper provides practical guidance to central banks on accounting practices for their foreign reserves, in connection with the transition from International Accounting Standard 39 Financial Instruments: Recognition and Measurement (IAS 39) to International Financial Reporting Standard 9 Financial Instruments (IFRS 9). The IFRS 9 preparation process can be summarized in three steps: (1) business model assessment and cash flow characteristic test for classification, (2) impairment, and (3) transition and disclosure preparation. Relative to IAS 39, IFRS 9 is more principles-based, which requires substantive management judgment, such as defining the business model, assessing significance and impracticability in applying exceptions, and determining expected credit loss methodologies. This paper focuses on step 3, transition and disclosure preparation, with an overview of the IFRS 9 transition requirements. A case illustration of a central bank making the transition demonstrates how the process is likely to impact a central bank’s foreign reserve portfolio.